Determinants of Bond Market Development in Nigeria - Jamilu Baita, Abubakar (Jurnal Ekonomi dan Bisnis Digital, 2024)
Capital market is of paramount importance in financing the activities of public and private sectors in both developed and developing economies. Consequently, this research analyzed the long run equilibrium relationships between bond market development (BMD) and a set of fiscal, macroeconomic and financial variables in Nigeria using Granger causality test and Johansen cointegration model. The findings reveal the importance of macroeconomic and financial variables in facilitating the development of Nigeria’s bond market. The study recommended that policy makers should ensure macroeconomic stability and financial soundness in order to develop bond market in the country.